Skepping deur evolusie - Ryke, P. a. J. (Koers, 1987)
Biblical Creation versus evolution has been an acrimonious issue for well over a century between religious conservatives, especially Protestant fundamentalists and those people who consider parts of the Bible - particularly the Book of Genesis - to be allegorical and symbolic. During the nineteenth century the idea that the Bible gave a directly true ac count of the origins of the world was deeply affected by scientific dis coveries. The new sciences of geology, and later of astronomy, made it overwhelmingly probable that the physical world is of in fin ite ly greater age than the few thousand years contemplated by the biblical account. The science of biology developed an account of the evolution of the various species of living organisms. Early fundamentalism was savagely hostile to the theory of evolution. In the m id-twentieth century the strife over this question seemed to have died down; but in the seventies and eighties hostility to evolution flared up again, and theories of 'creationism' were deployed. Though creationism attempts to argue with scientific arguments against evolution, it is hardly to be doubted that the mainspring of its motivation lies in biblical fundamentalism: that is, people are creationists because they think that the theory of evolution contradicts scripture and that creationism agrees with it.